Human Capital and Energy Infrastructure: Implications for Economic Growth in Nigeria - Ogunjobi, Joseph O.; Eseyin, Oluwasegun; Popoola, Olabisi (International Journal of Energy Economics and Policy, 2021)
Both hypothetical and empirical evidences have found the roles that human capital and energy infrastructure in spurring the economic growth of a nation as very germane. These key variables are undoubtedly working together in a quest to achieve equitable redistribution of the nation’s economic resource and ensuring poverty reduction. This study is based on an attempt to use co-integration and ARDL modeling framework to examine the empirical evidence of the impact of the different components of human capital and energy infrastructure on economic growth in Nigeria between 1981 and 2018. Findings from the study showed that the quality of educational, transportation and communication facilities had a significant and contemporary influence on economic development. In the same way, investment in physical resources calculated by gross fixed capital development, quality of healthcare facilities, availability of power supply were also found to have a positive impact with a lag effect on economic growth. Implicitly, an increase in these facilities over the past decade in terms of their availability and efficiency would boost economic development over the current period. The study therefore recommended that education and health should be given an unwavering focus on investment by the policy maker as components of human capital coupled with energy infrastructure if the desired growth for which Nigeria aspires is to be attained. Keywords: Human capital, Energy Infrastructure, Economic Growth JEL Classification: F, O4, Q4 DOI: https://doi.org/10.32479/ijeep.10066